PERKEMBANGAN DAN EKSISTENSI HUKUM PIDANA ISLAM SEBAGAI SUMBER HUKUM DI INDONESIA - Hidayatullah, Syarif (SANGAJI: Jurnal Pemikiran Syariah dan Hukum, 2017)
The Islamic Law not only the low which realize in religious context, but also it become the resource law in constitution partly or generally. In civil law it is still particularly and generally, meanwhile in criminal law it does not concern seriously. Although, there are many problems which need to solve with the new innovative low especially in criminal, so the resource of law must be already to create peace and good manners. In this paper, writer use the juridical historical approach, which study about how propagation of Islamic Law as the resource of criminal law (jinayah), and how it gives idea and concept which make criminal law in Indonesia more propagate. Finally, it so helpful to criminal law in Indonesia